2014
DOI: 10.1016/j.endonu.2014.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Documento de consenso para la detección y manejo de la enfermedad renal crónica

Abstract: Chronic kidney disease (CKD) is an important global health problem, involving to 10% of the Spanish population, promoting high morbidity and mortality for the patient and an elevate consumption of the total health resources for the National Health System. This is a summary of an executive consensus document of ten scientific societies involved in the care of the renal patient, that actualizes the consensus document published in 2007. The central extended document can be consulted in the web page of each societ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 57 publications
(31 reference statements)
0
4
0
7
Order By: Relevance
“…Sin embargo numerosos estudios han demostrado una excelente correlación entre la EUA en 24 horas y el cociente albúmina-creatina en orina matinal puntual recogida después el descanso nocturno [17][18] . La variabilidad de la EUA a lo largo de día es muy elevada y puede ser superior durante el horario diurno (25 %) respecto al horario nocturno 19 , motivo por el cual se ha estandarizado la recogida de orina al levantarse el paciente por la mañana 20 .…”
Section: Daño Renalunclassified
See 1 more Smart Citation
“…Sin embargo numerosos estudios han demostrado una excelente correlación entre la EUA en 24 horas y el cociente albúmina-creatina en orina matinal puntual recogida después el descanso nocturno [17][18] . La variabilidad de la EUA a lo largo de día es muy elevada y puede ser superior durante el horario diurno (25 %) respecto al horario nocturno 19 , motivo por el cual se ha estandarizado la recogida de orina al levantarse el paciente por la mañana 20 .…”
Section: Daño Renalunclassified
“…La EUA también puede fluctuar día a día hasta un 40 % 20 , sobre todo en las fases iniciales, por lo que no es infrecuente observar que un paciente con EUA elevada en una determinación se normaliza posteriormente. Por ello, y para realizar un diagnóstico correcto, es necesario disponer de dos determinaciones de EUA patológicas en un intervalo de como mínimo tres meses.…”
Section: Daño Renalunclassified
“…Although it had appeared that the kidney has no share in hyponatremia development in SARS-CoV-2 infection previously, and most of the main mechanism of hyponatremia was SIADH. [25,26] Recently, it was reported that the kidneys are involved in SARS-CoV-2 -associated hyponatremia. Generally, it seems that there are 3 possible mechanisms that may lead to hyponatremia: excess ADH secretion either due to hypothalamic-pituitary-adrenal axis abnormality and/or ectopic ADH production due to SARS-CoV-2 pneumonia, and fluid plus sodium loss.…”
Section: 21mentioning
confidence: 99%
“…Nevertheless, despite their importance, invasive Rhodotorula infections are not well explained yet, few is known about the virulence potential of this yeast, and whether the dissemination process depends more of pathogenic merit of the fungus or the patient debility. In fact, CKD has become a serious public health problem, affecting 8 to 16% of the world’s population, it is responsible for high morbidity and mortality and represents a heavy financial burden for public health systems in developing and developed countries [16]. CKD implies in structural and functional renal deficiencies, which result in complex disorders.…”
Section: Introductionmentioning
confidence: 99%